Ekwiwalencja studiów zaocznych i stacjonarnych w opinii mojego środowiska = The equivalence of regular and in-training studies in the opinion of my academic circle - Dudzik, Maria (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article includes the empirical research connected with the in-training studies at the Polish Department of the Wrocław University.
Keywords: szkolnictwo wyższe; badania; Uniwersytet Wrocławski